1940
DOI: 10.3181/00379727-45-11789
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Iodine Therapy on Blood Iodine and Basal Metabolic Rate in Pregnancy.

Abstract: No definite correlation has been established so far between basal metabolic rate and the advance of pregnancy, but it is generally accepted that the basal metabolism tends to increase in pregnancy.This rise of B.M.R. may well be due to an acceleration of the activity of the thyroid gland in demand for increased iodine requirements during pregnancy. Maurerl and Bokelmann and Scheringer2 have reported increased bIood iodine values during the' latter part of pregnancy.For our study, Stevensys method has been used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1950
1950
1950
1950

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Many investigators have confirmed an elevation of the total blood iodine and of the PBI, associated with the gland hyperplasia (19,27,100,125,134,135,140,141,142,143). It has been stated that this may represent an accentuation and prolongation of the rise observed between menstrual cycles (134).…”
Section: Pregnancy and Sterilitymentioning
confidence: 84%
See 1 more Smart Citation
“…Many investigators have confirmed an elevation of the total blood iodine and of the PBI, associated with the gland hyperplasia (19,27,100,125,134,135,140,141,142,143). It has been stated that this may represent an accentuation and prolongation of the rise observed between menstrual cycles (134).…”
Section: Pregnancy and Sterilitymentioning
confidence: 84%
“…Although it appears reasonable that extra iodine may be needed to provide sufficient hormone to allow for the increased metabolism of a developing fetus, this therapy has not been based on good experimental evidence. David, Zener and Phetak (141,142,143) studied two groups of pregnant women, one a control and the other during iodine therapy (lipoiodine, 30 mg. daily). They concluded that during pregnancy a reciprocal relationship exists between the BMR and the blood iodine, a rise in one being accompanied by a fall in the other.…”
Section: Pregnancy and Sterilitymentioning
confidence: 99%